Needs Analysis to Develop Sound Waves Interactive Multimedia Teaching Material to Promote Student’s Conceptual Understanding and Technological Literacy - Arsy, Suci Annisya; Asrizal, Asrizal; Amir, Harman; Emiliannur, Emiliannur (Universitas Negeri Padang, 2025)
The rapid development of technology has brought significant changes in the world of education. Students are expected to be able to understand technology in learning. Based on observations conducted at SMAN 3 Solok, several problems were found in physics learning, including the limited availability of interactive digital teaching materials and low technological literacy and conceptual understanding of students. To address this, a needs analysis stage was conducted with a Research and Development (R&D) approach using the Hannafin and Peck model. Data were obtained from teacher questionnaires in the form of teaching material use, student questionnaires to determine student characteristics, technological literacy performance assessment sheets in the form of questions according to technological literacy indicators, and learning outcome documents to see student conceptual understanding. The results of the analysis showed that the teaching materials used were not yet technology-based, students' technological literacy skills were low, and student scores were still below the minimum completeness criteria. Based on these data, it is necessary to develop interactive multimedia teaching materials that integrate conceptual understanding and technological literacy.